Decision Support System Best Rider Si Penghubung Harapan (SPH) at Mini Station Tambaksari Ninja Express Surabaya - Umar, Muhammad Daffa; Junaedi, Lukman (PT Inovasi Pratama Internasional, 2025)
In the era of the industrial revolution 4.0, shipping services or expeditions have grown rapidly due to the increasing needs of people in online shopping. Ninja Express has facilitated several online stores or e-commerce and has many branches throughout Indonesia, one of which is the Tambaksari mini station. The Tambaksari mini station has several couriers who are tasked with delivering goods or what are called SPH riders (Si Penghubung Harapan). Every month there is a determination of the best SPH rider from each region based on the calculation of the performance of all SPH riders. The creation of this best rider SPH decision support system can facilitate the determination of the best SPH rider which was previously done manually. With the EXPROM II method, the system can compare several alternatives based on several established assessment criteria. The final calculation result is in the form of an alternative difference so that it can produce a ranking output based on the highest flow value. The implementation of this method is applied in web format using the PHP and MySQL programming languages.